Living in the non‐alcoholic fatty liver disease silent epidemic: a qualitative systematic review of patients' perspectives. Issue 4 (6th July 2022) - Ng, Cheng Han; Lim, Wen Hui; Chin, Yip Han; Yong, Jie Ning; Zeng, Rebecca Wenling; Chan, Kai En; Tan, Darren Jun Hao; Fu, Clarissa Elysia; Tang, Ansel Shao Pin; Goh, Lay Hoon; Devi, Kamala; Chew, Nicholas W. S.; et al.
Summary: Background: Non‐alcoholic fatty liver disease (NAFLD) affects one‐fourth of the global population. Yet, the care of these patients is limited and awareness of NAFLD remains low in the general public. Investigations into the lives of these patients are often forgotten and traditional quantitative studies only paint part of the picture. Aim: To assess the first‐hand accounts of these individuals and their perspective on living with NAFLD. Methods: A systematic search was conducted on Medline, Embase, CINAHL, PsycINFO and Web of Science database for qualitative literature regarding patients' perspectives on NAFLD. An inductive thematic analysis was conducted to generate themes and supportive subthemes. Results: We incuded eight articles in the review. There were three major themes including the impact on the quality of life, knowledge and information, and attitudes and perceptions on care. The impact of the quality of life details the emotional and physical distress of NAFLD. Knowledge and information include the lack of sufficient communication between healthcare providers and patients with a distinct knowledge gap. Attitudes and perceptions on care extrapolate the current active participation of patients and needs of the patients and the future care that they desire. Conclusion: This review synthesises first‐hand accounts of individuals with NAFLD. With the growing burden of NAFLD, future public interventions must consider individual views for success to be found. The identified themes serve as a forefront for consideration for public policies. Ultimately, NAFLD is a multisystem disease, which must be managed by a multidisciplinary team. Abstract : Graphical abstract on living in the NAFLD epidermic.